Multikultural dan Pendikan Islam - Saptorini, Endang; Andriyani; Dede Rosyada; Nurmalia Lusida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Multiculturalism is the acknowledgment and admiration of the variety of cultures present in a society. Islamic education that embraces multiculturalism imparts Islamic principles while also fostering respect and admiration for diverse cultures and religions. Multiculturalism is crucial for fostering cohesion and concord among religious groupings. The primary objective of multicultural education in Islam is to establish an all-encompassing educational setting where each student is esteemed and embraced, irrespective of their religion or cultural heritage. The multicultural method in Islamic education integrates global concepts, such as tolerance, justice, and peace, into the curriculum. This is accomplished by comprehending and valuing disparities through explicit teaching, collective deliberations, and engaging exercises. Furthermore, Islamic intercultural education places significant emphasis on the value of interfaith discourse as a means to enhance interfaith relations and eradicate preconceptions and prejudices. The implementation of multicultural education within the context of Islam encounters numerous obstacles. One of the criticisms comes from individuals who contend that education should be limited to a select group and uniform in nature. Proper implementation and dedication from all stakeholders can significantly contribute to the development of a more inclusive and harmonious society through multicultural Islamic education. Hence, implementing multicultural education in Islam is a prudent approach to foster cultural comprehension and foster tranquilly and concord in an ever more heterogeneous community.